2007
DOI: 10.1182/blood-2006-06-031088
|View full text |Cite
|
Sign up to set email alerts
|

Farnesyltransferase inhibitors inhibit T-cell cytokine production at the posttranscriptional level

Abstract: IntroductionSmall GTPases of the Ras family such as Ras, Rho, and Rac are important regulators of growth factor receptor-induced activation events in a variety of cellular systems. A hallmark of GTPases like N-, K-, and H-Ras is that several posttranslational modifications of the synthesized protein must occur before localization to distinct cell membranes is achieved, a necessary prerequisite for functional activity. 1 Prenylation catalyzed by 1 of 3 intracellular enzymes, farnesyltransferase (FTase) or geran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
30
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 36 publications
5
30
0
Order By: Relevance
“…In line with those observations are reported findings that inhibition of Ras activation results in the development of anti-inflammatory responses [15] and attenuation of experimental autoimmune disorders [14,18,19].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In line with those observations are reported findings that inhibition of Ras activation results in the development of anti-inflammatory responses [15] and attenuation of experimental autoimmune disorders [14,18,19].…”
Section: Discussionsupporting
confidence: 84%
“…Those data come from studies showing that mutations in distinct forms of Ras result, both in experimental animals and in humans, in a robust proliferative autoimmune phenotype [13]. In addition, recent data indicate that Ras inhibitors are capable of suppressing experimental autoimmune disorders in animals and favor a T helper (Th)1-dominated phenotype in lymphocytes [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Our observation that FTI reduced alloantigen-driven CD4 T-cell proliferation in vitro are, therefore, novel. Furthermore, we extended previous findings 29 by studying the in vivo effects of FTI and GGTI in a GvHD model. Thus the effects of an FTI and a GGTI on alloreactive immune responses that we GvHD protection by FTI and GGTI haematologica | 2013; 98(1) observed are beyond the previously reported in vitro findings using cell lines.…”
supporting
confidence: 67%
“…In vitro studies using murine Th1 and Th2 clones, stimulated in the presence of FTI, showed a dose-dependent reduction of lineage-specific cytokine secretion. 29 The cytokines analyzed in this study included IFN-γ, IL-2, IL-4 and IL-5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation